Cinderelas modernas: o que os best-sellers juvenis ensinam sobre ser mulher? - Reiss, Thamires Andrade (Universidade Federal de São Carlos, 2023)
Following Montserrat Moreno's provocation Como se ensina a ser menina, and the intersection between feminist studies and education, the research explores elements that shape the socialization of girls and women through the analysis of two contemporary Brazilian young adult literature works: Cinderela Pop by Paula Pimenta and Confissões de uma garota excluída, mal-amada e (um pouco) dramática by Thalita Rebouças. The guiding assumptions and companion texts of the research engage with the literature surrounding the evaluation of sexism in children's books based on discourse analysis. Thus, they indicate the cultural construction of gender relations, possible influences, and the potential of literature in processes of subjectivity and education. The analysis of the selected works highlights the authors' trajectory, the extratextual elements of their books as objects in relation to other cultural products, and an analysis of the representation of eight female characters, according to their significance in the respective plots. The results indicate that both works perpetuate ideals present in the Cinderella tale, such as the relentless pursuit of conformity to beauty standards, female rivalry in the pursuit of male love, women's personal fulfillment conditioned by romantic involvement with a man, compulsory heterosexuality, and the denial of sexuality. These elements perpetuate a Cinderella-inspired education. In light of this, the research also establishes initial ideas and proposes a decinderelizing education that promotes quality of life, freedom, and fulfillment for all women.
Modern Cinderellas: what do youth bestsellers teach about being a woman?
Keywords: Literatura Juvenil; Paula Pimenta; Thalita Rebouças; Relações de Gênero; Descinderelizar; Young Adult Literature; Gender Relations; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO